2003
DOI: 10.1590/s1516-35982003000800030
|View full text |Cite
|
Sign up to set email alerts
|

Valor nutritivo do feno de braquiária amonizado com uréia ou inoculado com Pleurotus ostreatus

Abstract: Verificou-se, mediante análises de composição química e ensaio de digestibilidade com ovinos, o efeito dos tratamentos químico (amonização com uréia) e biológico (inoculação com o fungo Pleurotus ostreatus) sobre o valor nutritivo do feno de Brachiaria decumbens. Ambos os tratamentos duraram 42 dias; após esse período, o feno foi seco e moído para fornecimento aos animais. As dietas experimentais foram: feno não tratado (FNT); feno não tratado + uréia (FNT + U); feno inoculado com fungo + uréia (FTB + U); e fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
13

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 11 publications
(6 reference statements)
0
6
0
13
Order By: Relevance
“…Ammoniation of the DM with 3% urea resulted in 38.4 ± 27.7% NDF degradation, which corresponds to an increase (P<0.0001) of 14.4% compared to the non-ammoniated hay, and agrees with that obtained by Paiva et al (1995b). These results indicate an effect of ammoniation on the cell wall, and a better utilisation of the fibrous carbohydrates, which may favour a tendency to increase DM intake (SCHMIDT et al, 2003) and availability of energy for the ruminants. Associated with these effects, the 10.2 ± 1.0 dA 17.1 ± 1.6 cA 51.5 ± 4.9 bA 74.9 ± 7.2 aA addition of NPN, readily available to microorganisms in the rumen, provides better conditions for the development of those rumen bacteria that potentially promote increased degradation of the fiber in the treated fodder (ROTH et al, 2010).…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…Ammoniation of the DM with 3% urea resulted in 38.4 ± 27.7% NDF degradation, which corresponds to an increase (P<0.0001) of 14.4% compared to the non-ammoniated hay, and agrees with that obtained by Paiva et al (1995b). These results indicate an effect of ammoniation on the cell wall, and a better utilisation of the fibrous carbohydrates, which may favour a tendency to increase DM intake (SCHMIDT et al, 2003) and availability of energy for the ruminants. Associated with these effects, the 10.2 ± 1.0 dA 17.1 ± 1.6 cA 51.5 ± 4.9 bA 74.9 ± 7.2 aA addition of NPN, readily available to microorganisms in the rumen, provides better conditions for the development of those rumen bacteria that potentially promote increased degradation of the fiber in the treated fodder (ROTH et al, 2010).…”
Section: Resultsmentioning
confidence: 79%
“…With the DM ammoniated with 3% urea, the NDF content of the hay was lower when fertilising with 40 or 120 kg N ha , which may be related to the increase in leaf-area index due to the increase of N in the fertiliser, with the leaves having a lower ADF content in relation to the stem. Ammoniation with 3% urea reduced (P<0.0002) the ADF content compared to the untreated hay, irrespective of the level of N in the fertiliser, an effect caused by the breakdown of ester bonds between molecules of structural carbohydrates, also seen by Schmidt et al (2003) and Gobbi et al (2005) in hay from signal grass (Brachiaria decumbens) and Zanine et al (2006) , when the HCEL content of the ammoniated hay exceeded that obtained for the non-ammoniated, due to the proportionally lower ADF content (Table 3) in relation to the NDF (Table 2). Gomes et al (2009) observed an increase in the NDF content of carnauba straw (Copernicia prunifera) with the DM ammoniated with up to 10% urea, and Schmidt et al (2003) obtained an increase in HCEL content for hay from signal grass ammoniated with 5% urea, compared to the untreated hay.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Outro fator é que as diferentes dietas experimentais (Tabela 1) apresentaram valor acima do nível mínimo de 7,0% de PB, que é exigido para o normal funcionamento ruminal (Silva e Leão, 1979). Em trabalho realizado com feno de Brachiaria decumbens, Schmidt et al (2003) não observaram efeito na ingestão de MS para os fenos amonizados com valores médios de ingestão de 1,87% do PV, porém os animais Acta Sci. Anim.…”
Section: Resultados E Resultados E Resultados Eunclassified
“…A fenação de gramíneas, em estádio avançado de maturidade, resulta em forragem de baixo valor alimentício. Apesar de boa produção de matéria seca (MS), nesse período, as plantas apresentam alto teor de fibra e baixo teor de proteína bruta (PB), resultando em um material de baixa digestibilidade da matéria seca (Schmidt et al, 2003).…”
Section: Introdução Introdução Introdução Introduçãounclassified